An Evidence Based Clinical Study on Homoeopathic Treatment of Hepatitis B Patients (Advancements in Homeopathic Research, 2022)
This retrospective study was done on the confirmed patients of Hepatitis B treated with homoeopathic medicines in Gaurang Clinic & Centre for Homoeopathic research, Lucknow, India. Eighteencases were found fit for the study who properly followed the treatment with regular investigations. Objective: To explore the efficacy of Homoeopathic medicines in treatment of Hepatitis-B patients. Material and Methods • Eighteen diagnosed cases of Hepatitis B. • Homoeopathic medicines prescribed as per constitution of the patient along witha few organ remedies. • Follow up assessment was done with HBV DNA Quantitative (Viral load) test. Results Out of 18 patients,14 have shown positive response to the treatment; in 5 cases considerable reduction in viral load was observed whereas in other 9 cases, viral load came to below detection limit after treatment. Two casesremained status quo and two case did not improve.
Keywords: Homoeopathic Treatment; Hepatitis B; Clinical Study